Meningkatkan Motivasi Belajar Melalui Aplikasi Kipin School Berbasis Media Buku Elektronik pada Peserta Didik Kelas III Sekolah Dasar - Putri, Rizkia Rima; Kuntarto, Eko; Rosmalinda, Desy (Universitas Batanghari Jambi, 2024)
This study aims to describe efforts to increase student learning motivation in the content of Civics class III Elementary School using the Kipin School application conducted at SD Negeri 150/IX Mekar Sari. This research is a class action research (PTK) consisting of two cycles, the data taken in the form of observation data through the observation sheet of learning motivation using the electronic book media application, namely Kipin School. This research was conducted with 4 stages, namely planning, implementation, observation, and reflection. The results of this study indicate an increase in student learning motivation seen from the observation sheet in cycle I student learning motivation of 50%. Then increased to 93% in cycle II. Based on the findings of the research results, it can be concluded that the learning motivation of students using electronic book media through the Kipin School application for grade III elementary schools can increase.